Low back pain is closely associated with frailty but not with sarcopenia: Cross‐sectional study of rural Japanese community‐dwelling older adults. Issue 1 (27th November 2020) - Tsuji, Shotaro; Shinmura, Ken; Nagai, Koutatsu; Wada, Yosuke; Kusunoki, Hiroshi; Tamaki, Kayoko; Ito, Masako; Sano, Kyoko; Amano, Manabu; Hasegawa, Yoko; Kishimoto, Hiromitsu; Maruo, Keishi; et al.
Abstract : Aim: We speculated that low back pain, which is the most common ailment in older adults, is associated with frailty and/or sarcopenia and contributes to the progression of either condition. Our objective was to evaluate the relationship between low back pain, sarcopenia and frailty in rural Japanese community‐dwelling older adults. Methods: We recruited 730 participants aged ≥65 years who underwent a comprehensive health examination between November 2016 and December 2018. The Oswestry Disability Index (ODI) was used to assess low back pain quantitatively, and scores were compared for the frail groups determined by the Japanese version of Cardiovascular Health Study, and the sarcopenia groups as determined by the Asian Working Group for Sarcopenia 2019. Results: Among 730 participants, the prevalence of low back pain was 57.8%. There were significant differences in the ODI scores between the robust, prefrail and frail groups ( P  < 0.001). In contrast, there were no significant differences in the ODI scores among the robust, low appendicular skeletal muscle and sarcopenia groups. Logistic regression analysis showed that the prevalence of low back pain and the ODI scores were significantly associated with frailty after adjustment for age, sex and body mass index (odds ratio 3.41, 95% confidence interval 1.39–8.39, P = 0.008, and odds ratio 1.06, 95% confidence interval 1.04–1.09, P < 0.001, respectively). Conclusions: To the best of our knowledge, this study is the first to show the close association between low back pain and frailty, and suggests that not only the decline in physical function but also neuropsychiatric factors, including chronic pain, constitute a vicious cycle of frailty in community‐dwelling older adults. Geriatr Gerontol Int 2021; 21: 54–59 .